Spirituality as a Dimension in Counselling - Wong, Peter, Sin On (INTI Publishing House Sdn. Bhd., 2006)
The purpose of this paper is to examine the vitality of the spiritual dimension of the human person and its centrality in counselling. Spirituality is differentiated from religion as every person can be said to have his own sense of spirituality, even though the person may be an atheist; not everyone adheres to religious beliefs. A brief historical overview of how spirituality and religion have evolved ¡n their roles within the context of mental health, specifically in counselling is addressed. While many proponents of mental health theories highlight the idea of spiritual dimension as a major or an indispensable dimension, not everyone agrees on the debate, and an antithesis is discussed.